Passive transfer of Plasmodium falciparum MSP-2 pseudopeptide-induced antibodies efficiently controlled parasitemia in Plasmodium berghei-infected mice (2009)
We have developed monoclonal antibodies directed against the pseudopeptide ?-130, derived from the highly conserved malarial antigen Plasmodium falciparum merozoite surface protein 2 (MSP-2), for obtaining novel molecular tools with potential applications in the control of malaria. Following isotype switching, these antibodies were tested for their ability to suppress blood-stage parasitemia through passive immunization in malaria-infected mice. Some proved totally effective in suppressing a lethal blood-stage challenge infection and others reduced malarial parasitemia. Protection against P. berghei malaria following Ig passive immunization can be associated with specific immunoglobulins induced by a site-directed designed MSP-2 reduced amide pseudopeptide. © 2008 Elsevier Inc. All rights reserved.